DAMPAK MOTIVASI KERJA, DISIPLIN KERJA, KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT CAHAYA SURYA EKSPRESS - Reza Wahyu Firmansah; Wahyu Eko Pujianto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to determine the test results of the influence of Motivation, Dicipline, Leadership on Kinerja Karyawan di PT Cahaya Surya Ekspress. The research method used is the associative method with a quantitative approach using the Statiscial Program for Social Science (SPSS) 25 analysis tool to measure the results of Motivation, Dicipline, Leadership, as the independent variable, Kinerja Karyawan as the dependent variable. This study uses the sampling technique used, namely purposive sampling with 46 respondents staff PT Cahaya Surya Ekspress. The results of this study indicate that the influence of Motivation, Dicipline, Leadership has a significant effect on Kinerja Karyawan.